Antibacterial activity of a scorpion-derived peptide and its derivatives in vitro and in vivo. (30th October 2020) - Li, Zhongjie; Yuan, Yaping; Li, Shasha; Deng, Bo; Wang, Yong
Abstract: Antimicrobial peptides have recently become extremely popular as a novel class of antimicrobial agents. AMP MK049518 (FLGLLGSVLGSVLPSIFK), identified from the crab-scorpion Didymocentrus krausi, only possesses significant antibacterial activity against Gram-positive bacteria. In this study, a derivative G2K–S3K was designed with an excellent antibacterial spectrum and significantly higher antibacterial activity compared to the natural peptide. G2K–S3K also demonstrated excellent serum- and thermal-stability and did not induce bacterial resistance. In the Staphylococcus aureus and Pseudomonas aeruginosa -induced skin infection in mice, G2K–S3K significantly decreased bacterial counts in the wound by topical application. Thus, G2K–S3K could be a potent topical anti-infective agent against the skin infection caused by S. aureus and P. aeruginosa . Highlights: Scorpion venoms have been good resources for the discovery of antimicrobial peptides. A scorpion-derived peptide, G2K–S3K, with improved antibacterial spectrum and activity was designed in this study. G2K–S3K showed excellent serum- and thermal-stability and did not induce bacterial resistance. G2K–S3K could significantly decrease the counts of Staphylococcus aureus and Pseudomonas aeruginosa in the wounded region. G2K–S3K could be a potent topical anti-infective agent against skin infection.